Determination of Motivational Factors Affecting Employee Turnover Intention: With Reference to Manufacturing Sector of West Malaysia - Santioso, Valiandra (2014)
Corporations in Malaysia are actively looking to improve their employee value proposition to attract skilled worker with offering faster growth opportunity and higher salaries. Convenient methodology used for sample group of 200 Malaysian employees of several manufacturing companies. A questionnaire is developed to measure and test the impact on motivation toward turnover intention. Correlation analysis is used to identify the influence from response variable. Regression analysis is used to examine the relationship of the independent variable towards the employee motivation. The employee turnover rate in Malaysia increase from 12.3% in 2012 to be 13.2% in 2013, which is considered a high turnover rate. Among all industries, manufacturing is the major contributors towards Malaysia national gross domestic product. Turnover can cause instability in organizational structure as well as a direct impact on business performance. According to Malaysian statistic, reduction of total number of employees will impact on reduction of value output. This research aims to identify factor(s) that contribute to intrinsic and extrinsic motivation. Another objective of this research is to identify the impact of intrinsic motivations toward turnover intention. It is found that job satisfaction and perception of individual ability is the intrinsic motivational factor and the working environment is extrinsic motivational factor.